Juru Sembelih Halal Berbasis Pada Walisongo Halal Research Center (WHRC) - Solek, Mohamad (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
In everyday life, we canâ€™t escape from eating meat, but sometimes we often question about the status of halalness, that is whether it meets the criteria of halal slaughter according syara' or not yet. The effort to realize the halal slaughter is to conduct Halal Slaughter Training marching at the Walisongo Research Center for students of Walisongo State Islamic University of Semarang.The halal slaughterhouses training activities are designed in the form of intensive and continuous training accompanied by expert of the Food and Cosmetics Review Institute (LP POM) of Central Java MUI, experts of the Livestock and Animal Health Service (DISNAKKESWAN) and Walisongo Halal Research Centre (WHRC).The results of this dedication in the implementation of the halal slaughterer training is that students are able to understand the halal slaughtering way (according to Syaraâ€™ and MUI Standard) and be able to practice a professional halal slaughterer, while the sustainability of this training is Student/graduate of Walisongo State Islamic University of Semarang as â€œProfesional Halal Slaughtererâ€ in their regions.Â Dalam kehidupan sehari-hari kita tidak bisa lepas dari mengonsumsi daging, namun terkadang kita sering mempertanyakan tentang status kehalalan tersebut yaitu apakah sudah memenuhi kriteria penyembelihan halal sesuai syaraâ€™ atau belum. Upaya untuk mewujudkan penyembelihan halal tersebut adalah dengan mengadakan Pelatihan Juru Sembelih Halal berbasis pada Walisongo Halal Research Center (WHRC) bagi mahasiswa UIN Walisongo Semarang. Kegiatan pelatihan juru sembelih halal tersebut didesain dalam bentuk pelatihan yang dilakukan secara intensif dan kontinu dengan didampingi oleh tenaga ahli Lembaga Pengkajian Pangan Obat-obatan dan Makanan (LPPOM) MUI Jawa Tengah, tenaga ahli Dinas Peternakan dan Kesehatan Hewan (DISNAKKESWAN) dan tenaga ahli Walisongo Halal Research Center (WHRC). Hasil kinerja pengabdian dalam pelaksanaan pelatihan juru sembelih halal yaitu Mahasiswa mampu memahami cara menyembelih yang halal (sesuai Syaraâ€™ dan Standar MUI) dan mampu mempraktekkan menjadi juru sembelih yang halal profesional, adapun keberlanjutan pelatihan ini adalah Mahasiswa/Alumni UIN Walisongo Semarang sebagaiâ€œJuruSembelih Halal yang Profesionalâ€ di daerah asalnya masing-masing.